2015
DOI: 10.1037/a0037860
|View full text |Cite
|
Sign up to set email alerts
|

Record-informing and note-taking: A continuation of the debate about their impact on client perceptions.

Abstract: This article was written as a continuation of the debate between Mills (2012) and Dobson (2011, 2012) on record-keeping practices, specifically informing clients of their right to access their records and taking notes during sessions. Prior research has found that clients react positively to being shown their records, but no studies have examined the impact of informing clients of their right to access their records. Research on note-taking has been mixed, showing either a negative impact or no impact. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Other studies have failed to find a difference. For example, Christie, Bemister, & Dobson [53] created therapy videos in which the therapist either took occasional notes (8 times during a 9-minute video) or took no notes. Participants' competency ratings of therapists who took notes did not differ from ratings of therapists who did not take notes.…”
Section: Hospital Roommentioning
confidence: 99%
“…Other studies have failed to find a difference. For example, Christie, Bemister, & Dobson [53] created therapy videos in which the therapist either took occasional notes (8 times during a 9-minute video) or took no notes. Participants' competency ratings of therapists who took notes did not differ from ratings of therapists who did not take notes.…”
Section: Hospital Roommentioning
confidence: 99%
“…The empirical findings in these fields also lack consistency, which is likely a function of differing methodology and operationalization. For instance, some studies have found note-taking may influence rapport (Hartley, 2002; Hickling et al, 1984; Miller, 1992) while others do not (Christie et al, 2015). For example, Goldbloom (2011) argued the frequent pauses for note-taking has the ability to destroy the flow of an interview.…”
Section: Note-taking As An Interviewing Tool: Risks and Benefitsmentioning
confidence: 99%
“…When perceptions are measured using the "client" perceptions of note-taking, rather than a third party, note-taking does not seem to have the same negative influence. Christie et al (2015) examined the impact of note-taking on clients' perceptions of a therapist, whereby a large sample of undergraduate students viewed a video depicting a simulated therapy session. In the video, the therapist either took notes or did not take notes, and following the video, participants rated their perception of the therapist's effectiveness.…”
Section: Risk: the Effect On Rapport Buildingmentioning
confidence: 99%
“…If records have been viewed as serving the interests of the patient, what are the therapeutic and practical effects when records are now written to serve also the interests of third parties who may have different agendas, such as holding down costs, mandating or encouraging certain types of interventions, excluding treatment for certain disorders or problems, eliminating fraud and abuse, using the records to assess the competence and effectiveness of the therapist, compiling stats to make their agency look good, measuring "progress" in a way that is not meaningful or realistic for a particular patient, not allowing "preventive" interventions even when they might head off a foreseeable crisis, and so on? Research Christie et al's (2014) study providesd three valuable services to the field. First, it yielded empirical data addressing whether "[i]nforming clients of their right to access their records and taking notes during session .…”
Section: Third-party Payersmentioning
confidence: 99%
“…This article focuses on 5 challenging areas: confidentiality; informed consent; the state, the law, and legal requirements; third-parties; and the implications of research findings for record keeping. It discusses published claims, critiques, proposals for change, and research reports, particularly those of Bemister and Dobson (2011, 2012); Castonguay (2013); Christie, Bemister, and Dobson (2014); Furlong (2013); and Mills (2012). It emphasizes the potential problems with any “1 size fits all” approach and the difficulties in creating sensible regulations that do justice to the diversity of values, contexts, cultures, and theoretical orientations.…”
mentioning
confidence: 99%